Correlation between Maternal Age and Cesarean Section - Mastina Mastina; Herlin Fitriani K; Murdani Murdani (Universitas Aisyiyah Yogyakarta, 2019)
Maternal age at risk has increased over the past few decades, this is the same as the rate of labor in the cesarean section (WHO, 2014) the development of this trend reflects the views of women and advanced societies. Because there are many career and educational choices, women are motivated to continue pursuing their professional goals (Ramachandran et al., 2015). The purpose of this study was the correlation between medical indications and cesarean section delivery. The type of research used in this study was quantitative with a cross-sectional approach. Simple random sampling technique. Univariate analysis and bivariate analysis using the statistical test Chi-Square with a confidence level of 95% (α=0,05). After analysis using a Chi-Square statistical test with a confidence level of 95% (α=0,05) obtained p-value=0,004 which means that there is a correlation between the age of the mother with cesarean section delivery.